The Effect of Quail Feeders on Northern Bobwhite Density in Western Oklahoma - Stephen J. DeMaso; Darrell Townsend II; Scott A. Cox; Edward S. Parry; Robert L. Lochmiller (National Quail Symposium Proceedings, 2017)
We investigated the effect of quail feeders on northern bobwhite (Colinu s virginianus) covey size and density from I October 1991 to 1 October 1996 on the Packsaddle Wildlife Management Area (WMA ) in western Oklahoma. Thirty-two quail feeders tilled with milo were located near the center of every 8. 1 ha on a 283.3-ha treatment area. An adjacent 283.3-ha control area contained no quail feeders. Line-transect methodology was used to seasonally determine covey size and density on each area. Transects were traversed on horseback during October and March of each year. Mean fall covey size was similar (t = 0.19, df = 1, P = 0.8525) between the control (14.0 ± 1.2 birds/covey ) and treatment (14 .2 ± 1.1 birds/covey) areas, pooled over years . Mean spring covey size was similar (t = 10.18, df = 1, P = 0.9999 ) between the control (9.4 ± 1.9 birds/covey) and treatment (6.6 ± 1.5 birds/covey) areas, pooled over years . Pooled over treatments, mean covey size was similar (F = 1.30, df = 4, P = 0.2798) among years. but differed (F = 40.56, df = 1, P = 0.0001) between spring (7.6 ± 1.2 birds/covey) and fall (14.1 ± 0.8 birds/ covey). Mean bobwhite density, pooled over seasons and years was similar (t = -3.55, df = 1, P = 0.9125 ) between control ( 1.28 ± 0.43 birds/ha) and treatment (1.38 ± 0.44 birds/ha) areas. We concluded that quail feeders had no effect on mean covey size or density of bobwhite populations on our study area in western Oklahoma.
Keywords: Colinus virginianus. covey size. density. line tran sect. north ern bobwhite; OkJahoma . quail feeders